Psychological assessment of parents of people diagnosed with borderline personality disorder and comparison with parents of people without psychological disorders - Guillén, Verónica; Bolo, Sara; Fonseca-Baeza, Sara; Pérez, Sandra; García-Alandete, Joaquín; Botella, Cristina; Marco, José Heliodoro (Frontiers in Psychology, 2023)
Background: To date, several evidence-based interventions have been created to help relatives of people with Borderline Personality Disorder (BPD), but few studies have analyzed the clinical situation of the family members. The aim of this study was twofold: (1) to explore the clinical symptomatology in a sample of parents of people diagnosed with BPD and compare them with a sample of a sample of people without a relative with a personality disorder, (2) to explore whether the parents of people diagnosed with BPD have psychopathology related to personality disorders (PD) or meet the diagnostic criteria for PD. Method: Participants were 42 (39.6%) fathers and 64 (60.4%) were mothers and mothers (n = XX, –%) of people diagnosed with BPD, who were selected from a specialized PD unit for treatment. The sample of people without a relative with a PD was obtained from social network announcements. To test for differences between the two groups, Student's t tests were performed for quantitative variables, and Chi-square tests were performed for categorical variables. Cohen's d was calculated as a measure of the effect size. Results: Parents of people with BPD showed greater depressive and anxious symptomatology, higher levels of expressed emotion, and worse quality of life than the sample of people without a relative with a personality disorder. In addition, a high percentage of the parents of people diagnosed with BPD (50%) met the diagnostic criteria for different PD. Conclusions: Parents of people diagnosed with BPD may need psychological help in various aspects. Therapists are therefore advised to bear in mind the importance of carrying out a psychological assessment of family members and, if necessary, to offer psychological intervention. It is crucial to invite the family to be part of the treatment, since they can be part of the solution. Trial registration: ClinicalTrials.gov ID: NCT04160871. Registered November 15th 2019.